Analysis of Village Tourism Development in Sawahan, Trenggalek Regency, Indonesia: A Sustainable Livelihood Approach - Parmawati, Rita; Saktiawan, Yusup; Wibowo, Ferik Antyo Agus; Kurnianto, Agung Sih (E-Journal of Tourism; Volume 5 Number 1 (March 2018)DO - 10.24922/eot.v5i1.35181, 2018)
Sustainable approach  takes into consideration five aspects in the development of the model : social, natural, human, physical, and economic. This study aims to find out the Development of Tourism Village Based on Sustainable Livelihood Approach in Sawahan Village, Watulimo Subdistrict, Trenggalek Regency. The study was conducted on July-August, 2017 in Sawahan Village, Watulimo Subdistrict, Trenggalek Regency, East Java Province. The assumption is that the sustainable livelihood process has been running in the village. We observed 5 types of assets: naturalt, human, financial, social, and physical. The results are analyzed qualitatively as well quantitatively by statistical assumptions. We use the parameter significance test, which consists of testing the significance of parameters simultaneously and testing the significance of partial regression model parameters. Natural and social asset become the main factor in supporting the development of sustainable livelihood in Sawahan Village. Although it affects as minor condition, the financial, physical, and human asset can significantly influence when in the same condition.   Key Words : Asset, Livelihood, Sawahan, Sustainable